Destruction of Salivary and Lacrimal Glands by Th1-Polarized Reaction in a Model of Secondary Sjögren’s Syndrome in Lupus-Prone Female NZB × NZWF1 Mice - Hayashi, Toshiharu; Shimoyama, Natsumi; Mizuno, Takuya (Inflammation, 2012)
T helper (Th)1/Th2 balance determines the direction of some kinds of autoimmune diseases. The involvement of acini areas by CD4 + helper T(Th) cell subset in submandibular and lacrimal glands are largely unknown in secondary Sjögren’s syndrome (sSjS) with systemic lupus erythematosus (SLE). Submandibular and lacrimal glands were examined immunopathologically in lupus-prone female NZB × NZW(B/W)F 1 mice, model for human sSjS with SLE. Dacryoadenitis and sialoadenitis with renal failure developed with age. Infiltration of lymphoid cells (lymphocytes and plasma cells) expanded from the periductal areas in striated ducts to the acini, and the isolated foci in the acini were observed in those organs. The destruction of duct and acini epithelium, including the myoepithelium, was induced by interferon (IFN)-γ + and IgG2a + lymphoid cells, but not by interleukin(IL)-4 + , IL-5 + , IL-13 + , and IgG1 + lymphoid cells. Compared with IL-5 and IL-13, high values of IFN-γ were produced systemically at various ages. Also local expression of IFN-γ mRNA was higher than that of IL-4 mRNA. The result suggests that the acini destruction in submandibular and lacrimal glands may be induced by systemic and local Th1 cell dominant reactions in lupus-prone B/WF 1 mice with sSjS.